SISTEM INFORMASI BERBASIS WEB UNTUK KETERSEDIAAN PISANG LOKAL JAWA BARAT DI KAMPUNG CAU PADJADJARAN - Amili Yohari; Irfan Ardiansah; Dwi Purnomo (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2019)
Kampung Cau Padjadjaran (KCP) is an agency and bananas distributor that has the empowerment and utilization activities of local bananas. KCP partnered with several villages in the cities and districts of West Java, such as Sumedang, Sukabumi, Tasikmalaya, Garut, and Purwakarta. Up to now, KCP need to fulfill the market demand reaches 10 tons per week. Currently, KCP collects the data directly by visiting each village partners that each village is far enough to be visited, these are considered inefficient because it can be a waste of time and energy on the go and also the 10 tons bananas data per week is a high amount of data to be managed. To facilitate the achievement of the KCP objectives as a unit that raises superior local wisdom, hence the design of the web-based information systems will be conducted that can be used to manage the KCP banana database. In addition, it is also expected to enhance the empowerment of local communities each village partner by managing the information systems. The designing is conducted through several stages, such as the early stage (field observations), the designing stage (needs analysis, user-interface web design, programming implementation) and the final stage (testing of information systems, research results and conclusion). The expected result is a system that empowers youth and improving the welfare of banana farmers by providing pertinent information availability of bananas each partner KCP village in West Java.